Community health workers' experiences of supervision by nurses at clinics in Limpopo Province - Makwena M. Matsi; Eucebious S. Lekalakala-Mokgele; Mary M. Madumo (AOSIS, 2023)
Background: Supervision of community health workers (CHWs) is considered, among others, a strategy to achieve universal healthcare globally. In South Africa, it is incorporated in the ward-based primary healthcare (PHC) outreach teams' policy and strategy, a national health insurance policy component. Supervision of CHWs by nurses in the policy is considered a measure to facilitate PHC service provision to communities. However, CHWs experienced varying levels of supervision from nurses and other workers globally and in South Africa. Aim: This study explored and described the experiences of CHWs about supervision received from nurses at PHC facilities in Limpopo Province. Setting: Participants were drawn from seven PHC facilities in Polokwane and Lepelle-Nkumpi subdistricts of the Capricorn District. Methods: A qualitative exploratory-descriptive and contextual study design was employed. Participants were selected utilising a purposive sampling method. Semi-structured interviews were conducted to collect data. Data were analysed according to themes and their associated categories. Measures to ensure rigour and ethical principles were applied. Results: Two main themes emerged: positive supervision experienced by CHWs and supervision challenges experienced by CHWs. Conclusion: The varying experiences of CHWs about supervision from nurses emerged and reflected the need for functioning supervision mechanisms. Contribution: The experiences of CHWs indicated inconsistent delivery of supervision by nurses in PHC facilities. The findings highlighted the need for effective supervision measures that are vital for the success of the CHW supervision programme.